Cardiopulmonary resuscitation at operating room entry in acute aortic dissection type A patients: is surgery contraindicated? - Isa, Hideki; Kanamori, Taro; Miyatani, Kazuki; Tsutsui, Masahiro; Ushioda, Ryohei; Yamanaka, Shota; Kamiya, Hiroyuki (Frontiers in Surgery, 2024)
This study aimed to compare the short-term outcomes of surgical treatment for acute type A aortic dissection between patients undergoing cardiopulmonary arrest at the time of entry into the operating room and patients who received successful preoperative cardiopulmonary resuscitation before entering the operating room or patients who had cardiopulmonary arrest on the operating room table after entering the operating room without cardiopulmonary arrest. In the present study, we focused on the circulatory status at the time of entering the operating room because it is economically and emotionally difficult to cease intervention once the patient has entered the operating room, where surgeons, anesthesiologists, nurses, and perfusionists are already present, all necessary materials are packed off and cardiopulmonary bypass have already been primed. Methods Twenty (5.5%) of 362 patients who underwent surgical treatment for acute type A aortic dissection between January 2016 and March 2022 had preoperative cardiopulmonary arrest. To compare the early operative outcomes, the patients were divided into the spontaneous circulation group (n=14, 70.0%) and the non-spontaneous circulation group (n=6, 30.0%) based on the presence or absence of spontaneous circulation upon entering the operating room. The primary endpoint was postoperative 30-day mortality. The secondary endpoints included in-hospital complications and persistent neurological disorders. Results Thirty-day mortality was 65% (n=13/20) in the entire cohort; 50% (n=7/14) in the spontaneous circulation group and 100% (n=6/6) in the non-spontaneous circulation group. The major cardiopulmonary arrest causes were aortic rupture and cardiac tamponade (n=16; 80.0%), followed by coronary malperfusion (n=4; 20.0%). Seven patients (50.0%) survived in the spontaneous circulation group, and none survived in the non-spontaneous circulation group (P=.044). Five survivors walked unaided and were discharged home; the remaining two were comatose and paraplegic.The outcomes were extremely poor in patients with acute type A aortic dissection who had preoperative cardiopulmonary arrest and received ongoing cardiopulmonary resuscitation at entry into the operating room. Therefore, surgical treatment might be contraindicated in such patients.